Preferensi Merek Sebagai Pemediasi Pengaruh Kesadaran Merek dan Asosiasi Merek terhadap Loyalitas Konsumen (Studi Produk Insektisida Merek Asmec 36 EC di Malang Raya) - Purwanto, Edi; Hadiwidjojo, Djumilah; Ratnawati, Kusuma (Jurnal Aplikasi Manajemen, 2013)
This study is directed to obtain empirical evidence about the effect of brand awareness and brand association toward brand preference and seek the role of brand preference as the mediating variable among brand association brand awareness toward brand loyalty. Population of this research is the assisted- farmers of PT.Agro Sejahtera Indonesia (Asterindo) located in Wajak ad Batu. The sample consists of 80 respondents. The data analysis used in the study utilizes path analysis. The results showed that brand awareness and brand association directly affect brand preferences and the preferences are able to mediate the influence of brand awareness and brand association to brand loyalty. To increase awareness and brandassociation, organization should improve the company's brand image through accessible media such as the internet, radio, and television. Companies need to conduct event marketing activities, such as directionalactivities and products trial on the field for mutual exchange of ideas and information to the fellow users; thus it will be able to create emotional bonds with brands. In addition, it needs to conduct an analysis on the map of competitors'strength related to the promotional activities maps undertaken.